TEM Study of Irradiated PVC Embedded with Tin Complexes of Heterocyclic and Aromatic Moieties - Anaheed A. Yaseen; Dina S. Ahmed; Dhuha H. Fadhil; Mohammed Kadhom; Muna Bufaroosha; Emaad T. B. Al‐Tikrity; Emad Yousif (Pusat Inovasi Sains, 2022)
Poly(vinyl chloride) (PVC) could be considered as one of the highly manufactured plastics with a production capacity of multiple millions tons per year. Fillers are recently added to PVC in an attempt to increase its applications in various sectors, especially at tough exposing conditions. Therefore, the current work reports the morphological studies of PVC sheets that contain trimethoprim-tin complexes as additives. The PVC was blended with a low concentration of trimethoprim-tin complexes and thin films have been prepared from the homogenous mixtures. The ultraviolet irritation impact on the morphology and physicochemical properties of the films was studied. It was found that the photodecomposition and photo-oxidation levels of PVC films were lower than the blank film’s ones. The TEM images showed that the undesirable changes in the surface of irradiated PVC films, such as the appearance of dark spots, cracks, and roughness, were minimized once the tin complexes were filled compared with the blank PVC.